The Unequivocal Dyad of Gut Microbiome and Osteo Integrity- Dynamic Cross-Talk and Implications in Osteoporosis Management: Pharmaceutical Science-Medical Biochemistry - S, Soumyakrishnan; M, Sreepriya (International Journal of Life Science and Pharma Research, 2022)
The gut microbiome is the consortia of microorganisms, viruses, fungi, bacteria and protozoa, that inhabit the gastrointestinal human tract. Many nonmodifiable and modifiable factors regulate the gut microbiota composition, which includes age, sex, medications, stress, environmental triggers and diet. The symbiotic relationship between the gut microbiome and the human host is crucial for mutual survival. The dysbiosis of gut microbiota is the underlying causative factor in the development of many inflammatory diseases. Bone is a dynamic organ, that continuously remodels throughout the entire life, maintaining an equilibrium between osteoblastic bone formation and osteoclastic bone resorption. The term “osteo microbiology” is rapid in emerging research that shows the roles of gut microbes in bone mineral density and skeletal integrity. The gut is a major source of water-soluble and lipid-soluble vitamins like B and K and it directly or indirectly influences bone remodelling and mineralization of the bone matrix. The gut microbiota like butyrate released metabolites to influence the actions of T regulatory cells, exerting an indirect effect on osteoblast proliferation and bone formation. In addition, the microbial metabolites generated by gut microbiota can inhibit osteoclastic activity and prevent bone loss. Thus, the gut microbiota can modulate bone remodelling equilibrium and protect the bone against metabolic diseases like osteoporosis (OP). The present review discusses the importance of the gut bone axis, modulation of this axis by active cross-talk between the gut microbiota and bone cascades, thereby enhancing the positive effects of skeletal integrity, bone health and OP management.